2021
DOI: 10.3390/ijerph18073575
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Roles of De Novo Lipogenesis in Breast Cancer

Abstract: In recent years, lipid metabolism has gained greater attention in several diseases including cancer. Dysregulation of fatty acid metabolism is a key component in breast cancer malignant transformation. In particular, de novo lipogenesis provides the substrate required by the proliferating tumor cells to maintain their membrane composition and energetic functions during enhanced growth. However, it appears that not all breast cancer subtypes depend on de novo lipogenesis for fatty acid replenishment. Indeed, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 141 publications
(100 reference statements)
2
26
0
Order By: Relevance
“…Consequently, suppressed c-Met signaling leads to the impaired downstream activity of the PI3K/AKT pathway and inhibits cell proliferation and apoptosis in these DLBCL cells [ 74 ]. Additionally, overexpression of FASN is not only involved in lipid synthesis but also in driving proliferation via extracellular regulated kinase 1/2 (ERK 1/2) and phosphatidylinositol-3′-kinase (PI3K/AKT), autophagy, DNA repair, lysosome biogenesis, cytoskeletal remodeling and metastasis [ 75 ]. Therefore, it is believed that de novo synthesized FAs are not released into the TME and are rather used for intracellular processes [ 71 , 72 ].…”
Section: Sources Of Lipids Within the Tumor Microenvironmentmentioning
confidence: 99%
“…Consequently, suppressed c-Met signaling leads to the impaired downstream activity of the PI3K/AKT pathway and inhibits cell proliferation and apoptosis in these DLBCL cells [ 74 ]. Additionally, overexpression of FASN is not only involved in lipid synthesis but also in driving proliferation via extracellular regulated kinase 1/2 (ERK 1/2) and phosphatidylinositol-3′-kinase (PI3K/AKT), autophagy, DNA repair, lysosome biogenesis, cytoskeletal remodeling and metastasis [ 75 ]. Therefore, it is believed that de novo synthesized FAs are not released into the TME and are rather used for intracellular processes [ 71 , 72 ].…”
Section: Sources Of Lipids Within the Tumor Microenvironmentmentioning
confidence: 99%
“…The DNL pathway is of particular interest as it plays a role in non-alcoholic fatty liver disease [ 173 , 174 ], obesity [ 6 , 175 ], insulin resistance [ 174 ], or cancer [ 176 ]. The process of DNL could be divided into several steps.…”
Section: Enzymes Of De Novo Lipogenesismentioning
confidence: 99%
“…Therefore, there is an urgent need to develop new treatment regimens or identify molecular targets for therapy. Recent remarkable advances in cancer metabolism research have revealed that reprogramming lipid metabolism is one of the hallmarks of cancer 2,3 . It has been reported that lipogenic enzymes are highly expressed in TNBC to obtain membrane phospholipids, signaling molecules, protein modifications, and energy for high proliferation 2,[4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent remarkable advances in cancer metabolism research have revealed that reprogramming lipid metabolism is one of the hallmarks of cancer 2,3 . It has been reported that lipogenic enzymes are highly expressed in TNBC to obtain membrane phospholipids, signaling molecules, protein modifications, and energy for high proliferation 2,[4][5][6][7] . Therefore, preclinical and clinical trials targeting lipid metabolism as a therapeutic target are proceeding 3,8,9 .…”
Section: Introductionmentioning
confidence: 99%